2013
DOI: 10.2147/cia.s50349
|View full text |Cite
|
Sign up to set email alerts
|

Effects of krill oil containing n-3 polyunsaturated fatty acids in phospholipid form on human brain function: a randomized controlled trial in healthy elderly volunteers

Abstract: BackgroundKrill oil, rich in n-3 (omega-3) polyunsaturated fatty acids (PUFAs) incorporated in phosphatidylcholine, has been reported to have many effects on physiological function. However, there are few studies using psychophysiological methods published that describe the effects of krill oil on brain function. We investigated the influence of ingestion of krill oil on cognitive function in elderly subjects by using near-infrared spectroscopy and electroencephalography.MethodsA randomized, double-blind, para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
92
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(96 citation statements)
references
References 37 publications
2
92
1
1
Order By: Relevance
“…The efficacy of LCPUFA on P300 amplitude, a secondary outcome, was not observed in the present study. Supplementation of 240 mg/day of ARA was effective on P300 amplitude 14 , but no effects on P300 amplitude were observed with 491 mg/day of EPA and 251 mg/day of DHA or EPA 193 mg/day and DHA 92 mg/day containing phospholipids 25 . Although further studies are needed, the effect of LCPUFA on P300 amplitude might be limited.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…The efficacy of LCPUFA on P300 amplitude, a secondary outcome, was not observed in the present study. Supplementation of 240 mg/day of ARA was effective on P300 amplitude 14 , but no effects on P300 amplitude were observed with 491 mg/day of EPA and 251 mg/day of DHA or EPA 193 mg/day and DHA 92 mg/day containing phospholipids 25 . Although further studies are needed, the effect of LCPUFA on P300 amplitude might be limited.…”
Section: Discussionmentioning
confidence: 87%
“…The importance of ARA is consistent with the report indicating that ARA was effective on P300 components in healthy elderly 14,26 . On the other hand, another study showed that EPA 193 mg/day and DHA 92 mg/day containing phospholipids supplementation for 12 weeks improved the P300 latency in elderly Japanese 25 . However, this efficacy was considered to be caused by the unique combination of EPA and phospholipids, because these doses of EPA and DHA were too low to increase blood EPA and DHA levels.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The physiological functions of this fat-soluble antioxidant have been widely documented in vitro, in vivo, and in pre-clinical studies and covered extensively for its health benefits in a recent review (Dose et al, 2016). AST associated to EPA and DHA has been demonstrated to have a great effectiveness for improving human brain function (Konagai et al, 2013), and neuro-protection (Barros et al, 2014). In this respect, Saw et al (2013), confirmed that low doses of AST combined with DHA or EPA have a synergistic antioxidant action mediated by the Nrf2 signaling pathway.…”
Section: Introductionmentioning
confidence: 99%